Evaluation Of The Application Of The Zoning System On Vehicle Flow Patterns At The Torobulu Ferry Port - Elfita Agustini; Febriansyah Febriansyah; I Putu Dicha Candra Pangestu (IWTJ : International Water Transport Journal, 2022)
Torobulu Ferry Port is a port located in Laeya District, South Konawe Regency, Southeast Sulawesi Province. This port connects between Konawe Selatan and Muna districts. At this time, the Torobulu Ferry Port has not implemented a zone system in accordance with applicable regulations, which causes many local residents to carry out activities in the port area, delivery vehicles or pick-ups are free to enter the port dock. a parking area ready to load vehicles and a parking area for shuttle vehicles, making delivery/pick-up vehicles often park in a ready-to-load parking area. To analyze this, an analysis based on the Minister of Transportation Regulation Number 29 of 2016 concerning Ferry Port Sterilization is used to analyze the zone system and the Decree of the Director General of Land Transportation Number SK.242/HK.104/DRJD/2010 concerning Technical Guidelines for Traffic Management Crossing for analysis of vehicle traffic flow patterns as well as analysis of the need for traffic signs supporting the zoning system and flow patterns referring to the Regulation of the Minister of Transportation Number 13 of 2014 concerning Traffic Signs. In order to create an orderly and safe ferry port, the results of the analysis are to establish a zoning system and regulate the traffic flow patterns of vehicles at the Torobulu Ferry Port and to support the zoning system and vehicle flow pattern settings, it is necessary to optimize facilities such as: adding tollgates, determination of parking areas for passenger/pick-up, determination of parking areas for ready-to-load vehicles, and traffic signs.